2019
DOI: 10.1158/0008-5472.can-19-0695
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Chromosomal Passenger Complex Subunit INCENP Induces Polyploidization, Apoptosis, and Senescence in Neuroblastoma

Abstract: Chromosomal passenger complex (CPC) has been demonstrated to be a potential target of cancer therapy by inhibiting Aurora B or survivin in different types of cancer including neuroblastoma. However, chemical inhibition of either Aurora B or survivin does not target CPC specifically due to off-target effects or CPC-independent activities of these two components. In a previous chromatin-focused siRNA screen, we found that neuroblastoma cells were particularly vulnerable to loss of INCENP, a gene encoding a key s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…This further reinforces transcriptional repression of RAD51 and thereby leads to highly reduced HR activity, which results in persistent DSBs and the generation of chromosome aberrations, senescence progression and its maintenance. Of note, also silencing of INCENP induced polyploidization, apoptosis, and senescence in neuroblastoma cells, highlighting the importance of proper CPC localization for the prevention of senescence [46]. Opposite, overexpression of wt-Survivin might enhance proper targeting of the CPC complex and reduce cytokinesis failure and senescence, thereby lowering TMZ-induced RAD51 and HR repression, which we could observe at RNA and, particularly, at protein level, where under overexpression of Survivin, RAD51 was stabilized.…”
Section: Discussionmentioning
confidence: 68%
“…This further reinforces transcriptional repression of RAD51 and thereby leads to highly reduced HR activity, which results in persistent DSBs and the generation of chromosome aberrations, senescence progression and its maintenance. Of note, also silencing of INCENP induced polyploidization, apoptosis, and senescence in neuroblastoma cells, highlighting the importance of proper CPC localization for the prevention of senescence [46]. Opposite, overexpression of wt-Survivin might enhance proper targeting of the CPC complex and reduce cytokinesis failure and senescence, thereby lowering TMZ-induced RAD51 and HR repression, which we could observe at RNA and, particularly, at protein level, where under overexpression of Survivin, RAD51 was stabilized.…”
Section: Discussionmentioning
confidence: 68%
“…The DNA damage response triggered after aurora kinase inhibition may direct the cells to repair the break, undergo apoptosis, or become senescent 25 . Immunostaining for the apoptotic marker cleaved caspase-3 showed abundant epithelial expression following Barasertib treatment compared with controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that these irregular nuclei arise with AURKB inhibitors because cells enter M phase and condense their chromosomes, yet they eventually decondense without proper segregation and form mostly single and irregular-shaped nuclei 20 . These chromatin aberrations are reported to increase the DNA damage response 25 and lead to cell death or cell cycle arrest in highly proliferating cells 39 . Our data demonstrate the formation of p.H2AX foci in the treated explants, suggesting that loss of AURKB rapidly predisposed the highly proliferating bud cells to double-strand DNA breaks (DSB).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that CDCA5, which is transcribed by E2F1, promotes oncogenesis by enhancing cell proliferation and inhibiting apoptosis via the AKT pathway in HCC [ 30 ]. In addition, INCENP dysregulation has also been confirmed to be related to the occurrence and development of a variety of tumors [ 31-34 ]. INCENP depletion can suppress neuroblastoma cell growth by inducing polyploidization, apoptosis, and senescence [ 31 ].…”
Section: Discussionmentioning
confidence: 99%